Unusual Atmospheric Phenomena Observed Near Channel Islands, UK, 23 April 2007 - BAURE, JEAN-FRANCOIS; CLARKE, DAVID; FULLER, PAUL; SHOUGH, MARTIN (Journal of Scientific Exploration, 2010)
Unusual atmospheric phenomena (UAPs) were observed in daylight by multiple observers on board two civil aircraft in widely separated locations. We summarise results of an investigation based on radio communications reporting events in real time to Air Traffic Control (ATC), ATC radar and weather radar recordings, Civil Aviation Authority (CAA) documents, witness interviews and statements, and other sources. We describe attempts to explain the phenomena with the help of expert specialist advisers and professional resources in the fields of meteorology, atmospheric optics, oceanography and geophysics. We are able to show that widespread media stories describing enormous phenomena up to a mile wide and detected by radar were based on speculation and misunderstandings. Many news reports were grossly exaggerated and inaccurate. However, we are unable to conclusively identify the UAPs observed. It proves possible to eliminate a number of theories with a fairly high level of confidence, leaving us with two types of phenomena—a rare atmospheric-optical effect or an earthquake precursor—both of which have the potential to explain at least some, although not all, features of the reports. We highlight certain features that appear to leave open the possibility of unusual physical processes. Keywords: UAP—atmospheric optics—anomaly—mirage—earthquake lights—EQL